PENINGKATAN KESADARAN MASYARAKAT TERKAIT SANITASI MELALUI PENGENALAN FILTER AIR BAKU SEDERHANA - Hidayat, Habibi; Koda, M. Idris; Emilia (DHARMA BAKTI, 2024)
The residents of Bukur hamlet use water that is still classified as inadequate to meet their daily needs, especially for drinking water sources because there is contamination from the pipe system or water heater which is rusty or crosses water with the septic tanks found in Bukur hamlet. During observations and surveys carried out, many local residents still use water that is not suitable for drinking to meet their daily needs. If there is no awareness of how important clean water is and an understanding of making water sanitation equipment as one of the solutions that can be done to obtain clean water, then there will be even deeper problems regarding the health of these residents. This work program activity produces an understanding of how important it is to clean the water used to meet daily needs and produces solutions to obtain clean water through learning to make water sanitation equipment which can prevent users from various diseases that are affected by clean water.